Potential Antivirus Viral Nervous Necrosis Methanol extract of Amphora sp. in Cantang Grouper (Epinephelus sp.) - Ach. Khumaidi; Astik Umiyah (Samakia : Jurnal Ilmu Perikanan, 2019)
Cantang grouper received more serious attention from grouper fish farmers due to high export interest, but the attack of viral nervous necrosis (VNN) became a major obstacle in its cultivation. This study aims to explore the antiviral potential of diatom Amphora sp. to counter the VNN attack on Cantang groupers. The method used is the extraction of Amphora sp. with absolute methanol solvent. The extraction results were tested in vivo by giving Amphora sp. with different concentrations, namely: 17 µg / ml, 33 μg / ml, 50 μg / ml, and administration of extracts by challenging the 17 μg / ml + VNN, 33 μg / ml + VNN, 50 μg / ml + VNN. Fish treated with Amphora sp. also challenged by giving VNN Positive fish meat. During the period of rearing fish observed clinical behavior and symptoms. After the fish were raised for 15 days, the fish harvested were analyzed using histology, RT-PCR, and CPI methods (using the immuno ratio software) to see the HSP immune response obtained from the administration of Amphora sp. to find out its potential as a natural antivirus. From several test parameters, the concentration of extract 50 mg / ml + VNN was given to give the best response in the CPI analysis with a DAB value (61.3%). These results indicate that the methanol extract of Amphora sp. has the potential to be used as an antiviral candidate in Cantang grouper fish.